Roles of the lncRNAs MEG3, PVT1 and H19 tagSNPs in gastric cancer susceptibility - Esmat Abdi; Saeid Latifi-Navid; Vahid Kholghi-Oskooei; Behdad Mostafaiy; Farhad Pourfarzi; Abbas Yazdanbod (BMC Cancer)
Abstract Background Improper expression of long noncoding RNAs (lncRNAs) can cause various cancers. Single nucleotide polymorphisms (SNPs) affect the expression and function of several key lncRNAs. We assessed the associations of MEG3, PVT1, and H19 lncRNA polymorphisms with susceptibility to gastric cancer (GC). Methods In Ardabil (a high-risk area in North‒West Iran), 795 blood samples were collected from 396 cases and 399 controls. The control subjects were randomly selected from individuals receiving regular physical examinations in this hospital with no self-reported cancer history and were frequency-matched to the case group by sex and 5-year age intervals. All the samples were genotyped via the Infinium HTS platform, which was subsequently followed by rigorous data quality control, as well as statistical and bioinformatic analyses. Results The H19 rs2107425 SNP was associated with GC risk in a recessive model of inheritance (TT vs. CC + CT: OR = 1.87). The PVT1 rs13255292 variant in the overdominant model significantly reduced GC risk (CT vs. CC + TT: OR = 0.74). There was no significant association between H19 rs2839698, MEG3 rs116907618, or rs11160608, or PVT1 rs7017386, rs13254990 tagSNPs and susceptibility to GC. The interaction between H19 rs2107425 TT and PVT1 rs7017386 TC increased GC risk (OR = 3.73; pbon < 0.05). The MEG3, PVT1, and H19 variants were not associated with clinicopathologic characteristics. Conclusions We revealed significant associations of the H19 rs2107425 and PVT1 rs13255292 genetic variants with GC. Interestingly, the novel SNP‒SNP interaction of H19 and PVT1 tagSNPs had a greater effect than single SNP impacts did on GC risk, providing us with invaluable data to identify potential biological mechanisms involved in the development of GC.